Project Management Wytyczno: As an Example of Disseminating History in Public Space - Justyna MAŁYSIAK (Communications of International Proceedings, 2020)
In the area of public history, the implementation of scientific projects is becoming not so much a common practice in the modern world as it is necessary for the implementation of multi-track projects tailored to the expectations of increasingly demanding consumers. The preliminary research was to help to determine what kind of forms of history dissemination would be most appropriate in the course of a scientific-research project, as well as help to determine the level of knowledge about the Border Guard Corps and the battle of the Wytyczno in society, and thus help to take actions aimed at its intensification. Further research dedicated to the issue of history management in public space will certainly help to determine the most appropriate tools and processes that will influence the development of methodology for the professionalization of history education. Currently, this direction is in a constant phase of development, gaining more and more popularity especially in interdisciplinary areas.
Keywords: Management; Public History; Education; Project; Science.